Grain boundary character distribution in an additively manufactured austenitic stainless steel. (February 2021) - Laleh, Majid; Hughes, Anthony E.; Tan, Mike Y.; Rohrer, Gregory S.; Primig, Sophie; Haghdadi, Nima
Abstract: The grain boundary character distribution (GBCD) in an austenitic stainless steel produced by additive manufacturing (AM) in both as-built and annealed conditions was studied. Relatively fine grains and a non-fibre texture was achieved by AM, and as-built structure showed a high population of Σ3 boundaries. A five-parameter GBCD analysis revealed that the microstructure is mostly dominated by highly incoherent Σ3 boundaries. The grain boundary network also consisted of random high angle, coherent Σ3s terminating on (111) planes with a pure twist character, and tilt Σ9 boundaries. The findings show prospects for the possibility of engineering the grain boundary network of materials in-situ, via the stress and heat induced by the thermal cycles during AM. Graphical Abstracts: Graphical Abstracts Image, graphical abstract